Assessment of Clinical Presentation and Prognosis of Patients with Acute-On-Chronic Liver Failure among Participants Admitted in the Intensive Care Units of Tertiary Care Hospitals in Pakistan - Maliha Asim, Almas Sarwar, Adeel Anwar, Muhammad Hamid, Amber Amer, Usman Javaid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute chronic liver failure can be defined as a disease that is characterized as spontaneous deterioration of hepatic liver decompensation that was previously suffering from chronic liver conditions along with one or more than one organ failure extra hepatically which will consequently result in a risk of mortality. This study will focus on assessing the clinical and biochemical disease, cause, and outcomes of acute on chronic liver failure. Methodology: This cross-sectional study was conducted on 60 acute-on-chronic liver failure patients in the department of Internal Medicine, Holy Family Hospital, Rawalpindi and Lahore General Hospital of Pakistan from July 2021 to December 2021. Participants recruited for the study were presented with chronic liver disease with cirrhosis. Participants were divided into two groups, following admission into ward and the ICU. The participants were further divided into three groups according to acute on chronic liver failure. Patients were assessed for clinical outcomes and biochemical profiles of participants. Results: The outcomes of this study showed the primary etiology of chronic liver disease. The majority of participants forming group 2 of ICU had etiology of viral hepatitis C with a prevalence of 90% (n =27). The prevalence of viral hepatitis C etiology among participants was 96.7% with a number of participants being 29 of 30 in group 1. The most common aggravating factor for liver failure was bacterial origin in both ICU and ward with a prevalence of 80% and 76% respectively in both groups (n =24, n =23). The most common aggravating factor was observed to be a spontaneous bacterial infection in group two with a prevalence of 70% (n =21), whereas group one participants showed a prevalence of 63.3% (n= 19). The most common cause of organ failure among acute on chronic failure was most highly seen in the renal system with a prevalence of 60% among group 2 participants (n =18), whereas the incidence in group 1 was seen in 25 participants with a prevalence of 83.8%. Conclusion: The study concludes that the most common cause of the chronic liver disease is hepatitis c virus followed by hepatitis B virus. The most common aggravating factor for acute on chronic liver failure was spontaneous bacterial infection followed by a chest infection. The most common organ failure seen in participants was renal failure followed by cerebral failure.